2021
DOI: 10.1002/ima.22665
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning‐based method for automatic diagnosis of ankle fracture using X‐ray images

Abstract: Due to the complex mechanism of ankle injury, the clinical diagnosis of ankle fracture is extremely difficult. In order to simplify the fracture diagnosis process, this study proposes an automatic diagnosis model of ankle fractures. Firstly, an ankle fracture classification method suitable for machine learning was developed. By dividing six fracture regions, multiple types of fractures were clarified, and a corresponding dataset was created accordingly. Secondly, the random forest model was used to preprocess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this study, we introduced a dataset of annotated ankle x-rays and demonstrated the effect of its multiclass labeling by performing network training on the task of automated fracture detection on distinct subsets of images, thus quantifying the influence of selected image features. By utilizing customized state-of-the-art preprocessing and augmentation methods on both the images themselves as well as the composition of the training data set, our study performed better compared to most contemporary ankle studies, including both convolutional neural networks [ 16 , 17 ] and traditional machine learning methods [ 18 ]. For convolutional neural networks, the prevalent training protocol incorporates random dataset augmentation as performed in our study as well as triplication of the medical image for use on imagenet-pretrained networks.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we introduced a dataset of annotated ankle x-rays and demonstrated the effect of its multiclass labeling by performing network training on the task of automated fracture detection on distinct subsets of images, thus quantifying the influence of selected image features. By utilizing customized state-of-the-art preprocessing and augmentation methods on both the images themselves as well as the composition of the training data set, our study performed better compared to most contemporary ankle studies, including both convolutional neural networks [ 16 , 17 ] and traditional machine learning methods [ 18 ]. For convolutional neural networks, the prevalent training protocol incorporates random dataset augmentation as performed in our study as well as triplication of the medical image for use on imagenet-pretrained networks.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging serves as the principal method for diagnosing orthopedic conditions, including fractures, osteoarthritis, bone tumors, etc. [9]. Misdiagnosis, often due to image misinterpretation or misjudgment, is prevalent in clinical settings.…”
Section: Introductionmentioning
confidence: 99%